High Na+ Environments Impair Phagocyte Oxidase-Dependent Antibacterial Activity of Neutrophils - Krampert, Luka; Bauer, Katharina; Ebner, Stefan; Neubert, Patrick; Ossner, Thomas; Weigert, Anna; Schatz, Valentin; Toelge, Martina; Schröder, Agnes; Herrmann, Martin; Schnare, Markus; Dorhoi, Anca; et al. (Frontiers in Immunology, 2021)
Infection and inflammation can augment local Na+ abundance. These increases in local Na+ levels boost proinflammatory and antimicrobial macrophage activity and can favor polarization of T cells towards a proinflammatory Th17 phenotype. Although neutrophils play an important role in fighting intruding invaders, the impact of increased Na+ on the antimicrobial activity of neutrophils remains elusive. Here we show that, in neutrophils, increases in Na+ (high salt, HS) impair the ability of human and murine neutrophils to eliminate Escherichia coli and Staphylococcus aureus. High salt caused reduced spontaneous movement, degranulation and impaired production of reactive oxygen species (ROS) while leaving neutrophil viability unchanged. High salt enhanced the activity of the p38 mitogen-activated protein kinase (p38/MAPK) and increased the interleukin (IL)-8 release in a p38/MAPK-dependent manner. Whereas inhibition of p38/MAPK did not result in improved neutrophil defense, pharmacological blockade of the phagocyte oxidase (PHOX) or its genetic ablation mimicked the impaired antimicrobial activity detected under high salt conditions. Stimulation of neutrophils with phorbol-12-myristate-13-acetate (PMA) overcame high salt-induced impairment in ROS production and restored antimicrobial activity of neutrophils. Hence, we conclude that high salt-impaired PHOX activity results in diminished antimicrobial activity. Our findings suggest that increases in local Na+ represent an ionic checkpoint that prevents excessive ROS production of neutrophils, which decreases their antimicrobial potential and could potentially curtail ROS-mediated tissue damage.